The Gaia-ESO survey: galactic evolution of sulphur and zinc - Duffau, Sonia; Caffau, Elisabetta; Sbordone, Luca; Ludwig, Hans-Günter; Christlieb, Norbert; Koch-Hansen, Andreas (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 10.10.2017